Development of character education-based e-booklet as learning media on reproductive system material - Puput Oktariani; Miza Nina Adlini (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Electronic learning media based on character education, which results in the value of student character education, is still lacking. At the same time, some teenagers today have committed sexual harassment and negative behavior due to low character education. Therefore, it is necessary to have character education-based learning media, especially on reproductive system material. This study determines the validity, practicality, and effectiveness of character education-based e-booklets on reproductive system material. This study aims to produce character education-based e-booklets to determine the validity, practicality, and effectiveness of character education-based e-booklets on reproductive system material for students of class XI Vulpecula SMA Negeri 16 Medan. This research is a research and development (R&D) that uses the 4D model. This research was conducted at SMA Negeri 16 Medan for the academic year 2023/2024. Data were collected using validation sheets, teacher and student response questionnaires, and character education questionnaires for students. Furthermore, the data was collected using a Likert scale. This product was declared valid by media experts (93%), material experts (92%) and character education experts (91%). The results of the practicality analysis showed that the product developed was very practical, with the results for teacher responses (87%) and students' responses (92%). The analysis results of the student character education assessment obtained results (72%) that are developing. The advantages of the biology e-booklet on reproductive system material developed are that it is based on character education, is easy to understand, has an attractive design, and can improve learning outcomes. However, the religious indicators of students have not yet reached the highest criteria. Further research is needed to achieve a broader goal of shaping students' positive character education values.Abstrak. Media pembelajaran elektronik berbasis pendidikan karakter yang mengakibatkan nilai pendidikan karakter siswa masih kurang. Bersamaan dengan beberapa anak remaja zaman sekarang sudah melakukan pelecehan seksual dan tingkah laku negatif yang diakibatkan rendahnya pendidikan karakter. Maka dari itu perlu adanya media pembelajaran berbasis pendidikan karakter terutama pada materi sistem reproduksi. Penelitian ini bertujuan untuk mengetahui validitas, praktikalitas, dan efektivitas e-booklet berbasis pendidikan karakter pada materi sistem reproduksi. Penelitian ini adalah penelitian dan pengembangan (R&D) yang menggunakan model 4D. Penelitian ini dilakukan di SMA Negeri 16 Medan untuk tahun akademik 2023/2024. Data dikumpulkan menggunakan lembar validasi, angket tanggapan guru dan siswa dan angket pendidikan karakter untuk siswa. Selanjutnya data dikumpulkan menggunakan skala likert. Produk ini dinyatakan valid oleh ahli media (93%) ahli materi (92%) dan ahli pendidikan karakter (91%). Hasil analisis kepraktisan menunjukan bahwa produk yang dikembangkan sangat praktis dengan hasil tanggapan guru (87%) dan siswa (92%). Hasil analisis penilaian pendidikan karakter siswa didapatkan hasil hasil akhir (72%) sudah berkembang. Kelebihan dari e-booklet biologi materi sistem reproduksi yang dikembangkan karena berbasis pendidikan karakter, mudah dipahami, desain menarik, dan mampu meningkatkan hasil belajar. Namun, indikator religiusitas siswa belum mencapai kriteria tertinggi. Penelitian lebih lanjut diperlukan untuk mencapai tujuan yang lebih luas yaitu membentuk nilai pendidikan karakter positif peserta didik.